2005
DOI: 10.1007/s00775-005-0053-x
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic zinc-binding groups for use in next-generation matrix metalloproteinase inhibitors: potency, toxicity, and reactivity

Abstract: In an effort to improve the zinc-chelating portion of matrix metalloproteinase (MMP) inhibitors, we have developed a family of heterocyclic zinc-binding groups (ZBGs) as alternatives to the widely used hydroxamic acid moiety. Elaborating on findings from an earlier report, we performed in vitro inhibition assays with recombinant MMP-1, MMP-2, and in a cell culture assay using neonatal rat cardiac fibroblast cells. In both recombinant and cell culture assays, the new ZBGs were found to be effective inhibitors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 33 publications
2
83
2
Order By: Relevance
“…[40] IC 50 values were determined (Table 1) as previously described, [31,33,40] and enzyme kinetic experiments were performed to determine the K m value, K i value, and the mode of inhibition. As expected, MMPi 1-5 are poor inhibitors of shallow S1' pocket MMPs (that is, MMP-1 and MMP-7) with IC 50 values greater than 50 mm.…”
Section: In Vitro Efficacy Of Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[40] IC 50 values were determined (Table 1) as previously described, [31,33,40] and enzyme kinetic experiments were performed to determine the K m value, K i value, and the mode of inhibition. As expected, MMPi 1-5 are poor inhibitors of shallow S1' pocket MMPs (that is, MMP-1 and MMP-7) with IC 50 values greater than 50 mm.…”
Section: In Vitro Efficacy Of Inhibitorsmentioning
confidence: 99%
“…[22] Other efforts have been made toward the identification of alternative ZBGs using a novel bioinorganic approach. [18,[29][30][31][32][33] These studies have identified new ZBGs, that are more potent than hydroxamic acids, some of which have been developed into potent, nonhydroxamate inhibitors of MMPs. [32,34,35] In the present study, a series of hydroxypyrone and hydroxypyridinone inhibitors have been synthesized and evaluated to demonstrate that the isoform selectivity of an MMPi can be influenced by the choice of ZBG.…”
Section: Introductionmentioning
confidence: 98%
“…In these binding studies the coordination properties of the zinc binding groups of MMP inhibitors are investigated. In particular the pioneering work of Cohen Puerta & Cohen, 2003;Jacobsen & Cohen, 2004;Puerta et al, 2004;Puerta et al, 2005;Puerta et al, 2006;Jacobsen et al, 2007) and Vahrenkamp in this field has to be highlighted. Common zinc binding groups applied successfully in peptidase inhibitors have been either a carboxylic acid, a hydroxamic acid or a thiol functionality.…”
Section: Zinc Biomimetic Systemsmentioning
confidence: 99%
“…They reported the binding of β-mercaptoketone and β-mercaptoamide drugs in a bidentate fashion, while β-mercaptothiols bound exclusively in a monodentate manner, contrary to prior expectations . A whole series of publications by the same authors extended this concept to four different groups of chelators: hydroxypyridinones, pyrones, hydroxypyridinethiones and thiopyrones (Puerta & Cohen, 2003;Puerta et al, 2004;Puerta et al, 2005;Puerta et al, 2006;Jacobsen et al, 2007). Each of the tested small molecules was able to displace the hydroxide ligand in the [HB(pz Ph,Me ) 3 ]ZnOH model complex of the active site and to coordinate the zinc(II) in a bidentate fashion (Puerta & Cohen, 2003;Puerta et al, 2004;Puerta et al, 2006;Jacobsen et al, 2007) (Fig.…”
Section: Zinc Biomimetic Systemsmentioning
confidence: 99%
See 1 more Smart Citation